Re-positioning urban-based new villages in Malaysia towards sustainable living and a better quality of life - Phang, Siew Nooi; Tan, Teck Hong (2013)
A study into the history of New Villages (NV) in Malaysia indicates that there was a purpose and use for NVs when they were established and developed in the early 1950s.It was mainly to deter the communist insurgency and perceived support to the communists from the mainly Chinese peasants who were then relocated to these NVs in Selangor, Pahang, Johor and Perak. While initial assistance from the federal government did contribute marginally to the growth of these NVs, however, through the years, they were left to fend for themselves.Ultimately, the growth pattern of these settlements showed conspicuous disparity in terms of economic prosperity and development.What remained was the unchanged ethnic demographic component of these NVs which is still Chinese. The location of these NVs was also responsible to a great extent for their contrast in terms of wealth and economic prosperity. Those NVs nestled in semi urban and urban peripheries thrived and became robust, while those in the rural areas languished. Obviously, in the present context of Malaysia's rapid economic growth amidst political uncertainties, the existence of these NVs can be conceived either as a bane or a boon to the ruling government. Studies have thus far indicated that the actions taken by the relevant authorities in dealing with the socio-economic problems plaguing these settlements have suffered many shortcomings thereby reflecting negatively on both sides.Using a case study, this paper will explore and examine events that are challenging NVs in Malaysia which may alter the fate of NVs in the future.NVs in Malaysia today are at a cross-road between sustainable growth and fossilisation.The political process and the role of the local community can determine the outcome of the NVs and preliminary research for this paper will evoke several issues and findings to support this hypothesis.This paper will describe the living condition and housing environment of the NVs and narrate the political affinity of the NV community based on their voting patterns in the past general elections and groundwork investigations.Any re-development plans for the NVs should be viewed as a part of the mainstream of national development which has sustainable living and a better quality of life as one of the objectives.There has to be political will to ensure firm direction for matters pertaining to NVs and their future and their contribution to the overall nationhood building process of this country.